Switching and Frequency Response Assessment of Photovoltaic Drivers and Their Potential for Different Applications - Walid Issa; Jose Ortiz Gonzalez; Olayiwola Alatise (Micromachines, 2024)
Newly introduced Photovoltaic (PV) devices, featuring a built-in chip with an illuminating Light Emitting Diode (LED), have emerged in the commercial market. These devices are touted for their utility as both low- and high-side power switch drivers and for data acquisition coupling. However, comprehensive knowledge and experimentation regarding the limitations of these Photovoltaic Drivers in both switching and signal processing applications remain underexplored. This paper presents a detailed characterization of a Photovoltaic Driver, focusing on its performance under resistive and capacitive loads. Additionally, it delineates the device’s constraints when employed in signal processing. Through the analysis of switching losses across various power switches (Silicon and Silicon Carbide) in both series and parallel driver configurations, this study assesses the driver’s efficacy in operating Junction Field-Effect Transistors (JFETs). Findings suggest that Photovoltaic Drivers offer a low-cost, compact solution for specific applications, such as high-voltage, low-bandwidth measurements, and low-speed turn-on with fast turn-off power switching scenarios, including solid-state switches and hot-swap circuits. Moreover, they present a straightforward, cost-effective method for driving JFETs, simplifying the circuit design and eliminating the need for an additional negative power source.